2014
DOI: 10.1007/s00392-014-0778-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of β-blocker therapy on electrocardiographic and echocardiographic characteristics of left ventricular noncompaction

Abstract: Left ventricular noncompaction (LVNC) is a cardiomyopathy with hypertrabeculation of the LV, often complicated by heart failure, arrhythmia and thromboembolic events. The features of LVNC are still incompletely characterized due to its late recognition as clinically relevant condition. The aims of this study were to describe echocardiographic and electrophysiologic characteristics of LVNC patients and to assess the effects of chronic β-blocker treatment. Study patients (n = 20; 42.5 [36.3; 52.5] years; 12 men)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 39 publications
0
7
0
3
Order By: Relevance
“…Although few outcomes trials exist, in a recent study utilizing serial echocardiography, betablockers prevented the increase in left ventricular mass seen in the absence of therapy (64).…”
Section: Noncompaction In Adultsmentioning
confidence: 97%
“…Although few outcomes trials exist, in a recent study utilizing serial echocardiography, betablockers prevented the increase in left ventricular mass seen in the absence of therapy (64).…”
Section: Noncompaction In Adultsmentioning
confidence: 97%
“…На данный момент руко-водство по динамическому наблюдению и терапии СНМЛЖ не разработано, что во многом обусловлено отсутствием клинических исследований с достаточ-ным количеством пациентов. Проведенные исследо-вания охватывают только отдельные аспекты тера-пии, такие как назначение бета-блокаторов [34], антикоагулянтной терапии, имплантации импланти-руемого кардиовертера-дефибриллятора (ИКД). Было показано, что в группе пациентов с НМЛЖ наблюдается высокая частота развития сердечной недостаточности (NYHA III-IV) и ВСС [26,35].…”
Section: клиническая и молекулярная генетика нмлжunclassified
“…N-terminal pro-Btype natriuretic peptide has been measured only at baseline. 6 Bertini et al has shown that NCM patients with left bundle branch block with QRS duration of more than 150 ms or signs of left ventricular dyssynchrony to show some left ventricular reverse remodelling with resynchronization therapy. 7 We feel, however, that additional studies, especially in the light of newer heart failure therapies (i.e.…”
mentioning
confidence: 99%